2014
DOI: 10.1111/jpn.12197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soyabean meal‐ or whey‐based diets on lipid metabolism in weaned piglets

Abstract: The present study aimed to test the hypothesis that dietary protein source influences lipid metabolism-related parameters weaned piglets. The effects of soyabean meal (SB) and whey proteins (WP) on gene expression of several genes involved in the lipogenic process in liver, visceral (VAT) and subcutaneous (SAT) adipose tissues, plasma insulin concentration and fatty acid (FA) profile were investigated in 18 weaned piglets. Weaned piglets were fed one of two diets containing either SB or WP as the main protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Western blotting analysis showed that whey protein exerted no effect on LXR␣ protein levels. These results were consistent with those of a previous study, showing that whey-based diets fed to weaned piglets for 72 d exerted no effect on LXRs either in the liver or in adipose tissues (40).…”
Section: Discussionsupporting
confidence: 93%
“…Western blotting analysis showed that whey protein exerted no effect on LXR␣ protein levels. These results were consistent with those of a previous study, showing that whey-based diets fed to weaned piglets for 72 d exerted no effect on LXRs either in the liver or in adipose tissues (40).…”
Section: Discussionsupporting
confidence: 93%
“…Blood cholesterol level is largely determined by dietary fat and cholesterol intake, also high intakes of crude protein have been found to downregulate blood cholesterol (Theodorou et al, 2015). The general level of crude protein intake was higher in experiment 1 than in experiment 2, corresponding to lower blood cholesterol levels in experiment 1 as compared with experiment 2.…”
Section: Resultsmentioning
confidence: 99%
“…Whey powder has been supplied in swine diets ( Mahan, 1993 ; Yang et al , 2007 ). Several studies have been performed regarding the basic principle of dietary effect of whey protein on animals, including growth performance, nutrient digestibility, and its metabolic process ( Burnell et al , 1987 ; Grinstead et al , 2000 ; Kim et al , 2015a ; Theodorou et al , 2015 ). Ahmed et al (2014) noted that a positive effect of dietary whey protein on beef quality such as extended shelf-life of beef.…”
Section: Introductionmentioning
confidence: 99%